Experiential games developed by WLE/PIM/IFPRI/ICRISAT are being scaled out to almost 250,000 households to improve ground and surface water governance in India - CGIAR Research Program on Water, Land and Ecosystems (2019)
Rapid decline in groundwater levels is a serious challenge in many areas in India. WLE/IFPRI and PIM partnered with the Foundation for Ecological Security (FES), a major Indian NGO, to develop and test the use of experiential games to strengthen groundwater governance. ICRISAT developed similar tools for managing surface water. These tools were so successful that they will now be scaled out to over 3700 communities involving some 245,000 households in at least six Indian states.